2010
DOI: 10.1074/jbc.m109.056747
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the First Small Molecule Inhibitor of MDMX

Abstract: The p53 pathway is disrupted in virtually every human tumor. In ϳ50% of human cancers, the p53 gene is mutated, and in the remaining cancers, the pathway is dysregulated by genetic lesions in other genes that modulate the p53 pathway. One common mechanism for inactivation of the p53 pathway in tumors that express wild-type p53 is increased expression of MDM2 or MDMX. MDM2 and MDMX bind p53 and inhibit its function by distinct nonredundant mechanisms. Small molecule inhibitors and small peptides have been devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(168 citation statements)
references
References 38 publications
6
162
0
Order By: Relevance
“…Given this, effective elevation of p53 in tumors may well require a mixture of E3 ligase inhibitors tailored to the population of p53-directed ligases present in an individual tumor. Indeed, unique inhibitors that target both MDM2 and MDMX can impede growth and induce apoptosis in cells with high levels of both MDM2 and MDMX (26,31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Given this, effective elevation of p53 in tumors may well require a mixture of E3 ligase inhibitors tailored to the population of p53-directed ligases present in an individual tumor. Indeed, unique inhibitors that target both MDM2 and MDMX can impede growth and induce apoptosis in cells with high levels of both MDM2 and MDMX (26,31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Several small molecules inhibiting Hdm2 have been identified; however, these do not affect HdmX, impeding their efficiency, in particular in tumours with overexpressed HdmX. 16 An inhibitor of the HdmX/p53 interaction, SJ-172550 has been described recently; 19 it does not kill cancer cells on its own, but has an additive effect when combined with Hdm2 inhibitors. However, simultaneous targeting of Hdm2 and HdmX by a single molecule has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the chemical inhibitor of HdmX/p53 interaction, SJ-172550 has been found, which displays additive effects in cancer cells when combined with an Hdm2 inhibitor. 19 Wild-type p53-induced phosphatase 1 (Wip1), encoded by the PPM1D gene, is a serine/threonine phosphatase that exhibits oncogenic features. It is overexpressed in a vast number of tumours 20 and is important for tumour stem cell survival.…”
mentioning
confidence: 99%
“…Although they are homologs, it has been shown that Mdm2 and Mdm4 have distinct roles in the regulation of p53, 13 and we show that ES cells are another example where they have non-overlapping functions. Importantly small molecule inhibitors have been developed that can selectively block the p53 Mdm2 interaction and the p53-Mdm4 interaction 28,29 and it is important to understand the differential regulation of p53 by Mdm2 and Mdm4 to optimize their potential clinical use. We also demonstrate that our findings in ES cells are valid in the context of a whole organism.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%